Students’ perception through learning deductive and inductive in basic grammar - Kiptiyah, Mariyatul; Athena, Tera (Penerbit STKIP PGRI Bangkalan, 2019)
The inductive-deductive learning model is a learning model begins by giving examples with the aim that students can identify, differentiate, then interpret, generalize and finally draw conclusions. The objective of this study is to know the students perception to the application of Deductive and Inductive learning in Basic Grammar. The method that writer use is a qualitative research. Subject of the research are students at second semester of English Department. The result of the study showed there are 4% (2 students) answer strongly disagree, 12% (4 students) disagree, 21% (7 students) agree, 29% (10 students) agree and like this statement, and 34% (11 students) strongly agree using deductive and inductive learning.